2015
DOI: 10.1007/s10528-015-9684-y
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Maternal-Fetal Genetic Conflict Situations on the Pathogenesis of Preeclampsia

Abstract: Preeclampsia leads to maternal and perinatal morbidity and mortality. The literature in English was reviewed to summarize recent advances in understanding the global gene expression changes in the pathogenesis of preeclampsia. We identified at least eight consistently enriched categories, relating to pregnancy maintenance, metabolism, oxidative stress, cell cycle regulation, implantation, decidualization, immune modulation, and vascular function. Expression profiling in preeclampsia placenta and normal placent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…Although the placenta is the central organ for pathogenesis, epigenetic mechanisms in the placenta highlight the importance of a fine-tune orchestration of DNA methylation, miRNAs, histone modifications and chromatin structure (83). Recent epigenetic mechanisms associated with the dysfunction and dysregulation of decidualization-related genes have a critical impact on the susceptibility, development and progression of complex diseases, such as miscarriage, preterm birth, or preeclampsia (35,36,40). Furthermore, a previous study demonstrated that half of the decidualization-related genes in preeclampsia-affected placentas are downregulated and are also located within and in close proximity to known imprinted genes, suggesting an association between an epigenetic process and genomic imprinting in preeclampsia (36).…”
Section: Conclusion and Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the placenta is the central organ for pathogenesis, epigenetic mechanisms in the placenta highlight the importance of a fine-tune orchestration of DNA methylation, miRNAs, histone modifications and chromatin structure (83). Recent epigenetic mechanisms associated with the dysfunction and dysregulation of decidualization-related genes have a critical impact on the susceptibility, development and progression of complex diseases, such as miscarriage, preterm birth, or preeclampsia (35,36,40). Furthermore, a previous study demonstrated that half of the decidualization-related genes in preeclampsia-affected placentas are downregulated and are also located within and in close proximity to known imprinted genes, suggesting an association between an epigenetic process and genomic imprinting in preeclampsia (36).…”
Section: Conclusion and Considerationsmentioning
confidence: 99%
“…Compared to microarray-based analysis, RNA-seq can detect splicing isoforms and somatic mutations by taking advantage of a higher coverage and greater resolution (34). These approaches have identified the gene expression signatures and have predicted key pathways involved in preeclampsia-affected placentas (31,32,(35)(36)(37)(38). Although to date, at least to the best of our knowledge, there are relatively few available studies which have conducted gene expression analysis in preeclampsia-affected placentas using the RNA-seq method (32,33), a number of differentially expressed genes and their pathways have been shown to have the same direction of change.…”
Section: Gene Expression Profiling and Functional Pathway Analysis Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter results in maternal systemic disease through primary mediators, including oxidative stress and inflammation, and also secondary mediators, including modifiers of endothelial function and angiogenesis [ 5 ], leading to the clinical manifestation of preeclampsia. Genetic studies, such as microarray-based gene expression profiling studies, have been employed in the investigation of the pathogenesis of preeclampsia and differentially expressed genes have been identified [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%